Taxonomie Homogenization of the Freshwater Fish Fauna in Chile: Analyzing the Ichthyogeographic Provinces - Castro-Morales, S; Rojas-Montecinos, P (Springer International Publishing, 2021)
It is widely recognized that anthropogenic activity modifies habitat conditions and species composition in freshwater communities (Abell et al. 2008). The conservation status of the freshwater communities, and particularly of the freshwater fish fauna, is worrying because a massive compositional change in diversity is undergoing (Mack et al. 2000; Revenga et al. 2005; Dudgeon et al. 2006). The processes underlying this phenomenon can be reduced to mechanisms that promote the addition of new species (invasion or exotic species introduction) and the extinction or extirpation of the native ones (McKinney and Lockwood 1999; Olden and Poff 2003, 2004). As consequence, both invasions and extinctions are expected to contribute to taxonomic homogenization (McKinney and Lockwood 1999; Olden and Rooney 2006). The taxonomic homogenization is a process that can be defined as a temporal (or spatial) increase of the similarity (or spatial turnover) among communities that initially were more dissimilar (Olden et al. 2011; Toussaint et al. 2014). Currently, it is considered that the taxonomic homogenization is the first step of a more complex and complete process that includes ecological and evolutionary facets at different levels and scales (Olden et al. 2010, 2011). © Springer Nature Switzerland AG 2021. All rights reserved.